The social contract between the state and the citizen-migrant: EU free movement under a cosmopolitan statist lens - Francesca Strumia (European Law Open)
How does EU free movement alter the role of the sovereign state? While this question may not sound new, this Article addresses it from a novel angle. If from the perspective of host Member States free movement upgrades a class of migrants to the status of ‘migrant citizens’, from the perspective of home Member States free movement instead splits the class of the citizens into citizen–settlers and citizen–migrants. The Article explores how the social contract between the state and the citizen is rewritten in the wake of this latter transformation. It articulates the duty of the states as agents for the citizen–migrants. It flashes out the implications for the relation between citizen–migrants and citizen–settlers. And it points to the partly reflexive nature of duties of states and citizens towards non-citizen migrants. It thus ultimately sheds light on how free movement prompts the sovereign state to embrace cosmopolitan obligations towards others ‘from within’, as an indirect effect of advancing the transnational interests of the citizen–migrants. The findings ultimately add to the cosmopolitan statist vision of European integration, while also rephrasing some of the questions of solidarity, non-discrimination and participation that remain unanswered in the literature on Union citizenship and free movement.